Challenges and mitigation strategies for control of 3-MCPDEs and GEs in edible oil processing industries – A comprehensive review - Sanjay Kumar Singh; Neeraj P. Awasthi; P.K.S. Yadav (Food Chemistry Advances)
Process contaminants like mono or di ester of 3-monochloropropane-1,2-diol (3-MCPDEs) and glycidyl esters (GEs) formed during the process of refining of edible oils due to presence of required process conditions and various precursors have raised various food safety concerns because of their potential for negative health impact. These process contaminants are formed due to elevated operating conditions especially temperature and time. Unlike 3-MCPDEs which is impossible to remove, it is possible to either convert GEs to harmless compounds or to separate out the GEs in the refined oil. Many countries still do not have any set standards for these process contaminants in refined edible oils. However, these process contaminants concentration can be minimized following the certain strategies and advancement in processing technologies. This review paper deals with these process contaminants in detail along with their formation mechanism, sources of precursor, impact on health, global standards of these contaminants and their mitigation strategies.